Legislative means aimed at stimulating green procurement in the public sector: A critical case study of Romania - Ionel Bostan; Cristina Mihaela Lazar; Nicoleta Asalos (Amfiteatru Economic Journal, 2020)
In a framework characterized by a relatively high degree of institutionalization, such as that of the European Union, it became difficult to imagine that the problem of Green Public Procurement (GPP) could surpass it. The special importance of the GPP, due to its favorable effects on the sustainable development, conservation / improvement of the environment, human health, etc., to which other positive social-economic implications are added, makes it a distinct subject of both EU strategies / policies, and the related legislative system. In this respect, several directives, decisions and recommendations operate, which have obviously made a strong imprint on the policies and legislation of the Member States. Starting from the European requirements in the field, but also taking into account the regulatory framework applicable in Romania, our approach tackles legal instruments designed to stimulate GPP in the public sector, highlighting the dysfunctions in the field of green procurement special legislation. We consider here some delays in the application of the European legislation and related to the appearance of the guide containing the minimum criteria regarding environmental protection, etc., but also the existence of loopholes or contradictions in the legislative texts, as well as post-adoption deadlocks. In order to achieve the purpose of the paper, which is to demonstrate that the legislative means are capable of stimulating green procurement in the public sector, we carry out a review of the scientific literature, after which we focus on the European legislative system related to GPP. We then insist on the elaboration and implementation of national legal instruments aimed at stimulating the GPP and the arguments for strengthening the GPP system by regulatory means. Lastly, we saved an important part, that of the description of the special legal source intended to regulate the GPP in the national public sector, which is characterized by sluggishness, loopholes, post-adoption deadlocks. Our approach, in the structure shown, demonstrations that the regulatory body regarding the Romanian GPP system is characterized by inefficiency. According to the authors, the solution is implementing some legislative changes, strictly in accordance with the best European practices.
Keywords: K32; K39; Q56; Q59; R11; 330; green public procurement; regulatory system; legal loopholes; sanctions; inefficiency/inoperative law